Effects of combo therapy with coenzyme Q10 and mitochondrial transplantation on myocardial ischemia/reperfusion-induced arrhythmias in aged rats - Soleyman Bafadam; Behnaz Mokhtari; Alireza Alihemmati; Reza Badalzadeh (Iranian Journal of Basic Medical Sciences)
Objective(s): Ischemia/reperfusion (IR)-induced ventricular arrhythmia, which mainly occurs after the opening of coronary artery occlusion, poses a clinical problem. This study aims to investigate the effectiveness of pretreatment with coenzyme Q10 (CoQ10) in combination with mitochondrial transplantation on IR-induced ventricular arrhythmias in aged rats.Materials and Methods: Myocardial IR induction was performed by left anterior descending coronary artery occlusion for 30 min, followed by re-opening for 24 hr. CoQ10 was administered intraperitoneally at a dosage of 10 mg/kg/day for two weeks before inducing IR. At the start of reperfusion, 500 µl of the respiration buffer containing 6×106±5×105 mitochondria/ml of respiration buffer harvested from the pectorals major muscle of young donor rats were injected intramyocardially. To investigate arrhythmias, the heart’s electrical activity during ischemia and the first 30 min of reperfusion were recorded by electrocardiogram. After 24 hr of reperfusion, cardiac histopathological changes, creatine kinase-MB, nitric oxide metabolites (NOx), oxidative stress markers (malondialdehyde, total anti-oxidant, superoxide dismutase, and glutathione peroxidase), and the expression of genes regulating mitochondrial fission/fusion were measured.Results: Pretreatment with CoQ10 in combination with mitochondrial transplantation reduced ventricular arrhythmias, cardiac histopathological changes, and creatine kinase-MB levels. Simultaneously, this combined therapeutic approach increased myocardial NOx levels, fostering an improved oxidative balance. It also triggered the down-regulation of mitochondrial fission genes, coupled with the up-regulation of mitochondrial fusion genes. Conclusion: The combination of CoQ10 and mitochondrial transplantation demonstrated a notable anti-arrhythmic effect by elevating NOx levels, reducing oxidative stress, and improving mitochondrial fission/fusion in aged rats with myocardial IRI.